The Impact of Influencer Marketing on Consumer Buyer Behavior - Chiguvi, Douglas; Zhou, Noel; Molelekwane, Oratile; Mogae, Masego (International Review of Management and Marketing, 2025)
Influencer marketing has gained significant popularity in recent years. A social media influencer is an individual who has developed a substantial following in a specific industry and can influence others through their authenticity and reach. Brands are increasingly collaborating with social media influencers to engage target audiences, boost brand recognition, enhance brand image, and drive profitability. These influencers promote new products or emphasize a brand’s appeal through social media channels. This study aims to assess the impact of social media influencers’ credibility, attractiveness, trustworthiness, and expertise on consumer behavior at the Western University of Communication (WUC). The research employed a positivist philosophy and a quantitative approach. Data was collected through questionnaires from 320 respondents in Tlokweng, Mogoditsane, and Riverwalk, Botswana. Measures of central tendency, regression analysis, and correlation analysis were conducted using SPSS version 21. The results revealed that the expertise of social media influencers has a strong and significant impact on consumer behavior at WUC, followed by their attractiveness, trustworthiness, and credibility. Collectively, the four study variables namely credibility, attractiveness, trustworthiness, and expertise were positively and significantly linked to consumer behavior at WUC. The findings contribute to marketing literature by highlighting the importance of these attributes in shaping consumer behavior. Additionally, the study demonstrates the extent of influence social media influencers have on consumer behavior at WUC. Beyond theoretical implications, the findings also provide practical insights for digital marketing strategies involving social media influencers.